Cross‐sectional association of physical activity and periodontal antibodies. Issue 12 (10th August 2018) - Anderson, A. Paige; Park, Yong‐Moon; Shrestha, Deepika; Zhang, Jiajia; Liu, Jihong; Merchant, Anwar T.
Abstract: Background: The objective of this study was to evaluate the cross‐sectional association between physical activity and serum IgG antibodies against selected periodontal microorganisms. Methods: The study population consisted of 5, 611 randomly selected US adults who participated in the National Health and Nutrition Examination Survey (NHANES) III (1988 to 1994), who were 40 years and older with complete IgG antibody data against 19 oral microorganisms. We used cluster analysis to classify the 19 antibody titers into 4 mutually exclusive groups called "Orange‐Red, " "Red‐Green, " "Yellow‐ Orange, " and "Orange‐Blue, " and calculated cluster scores by summing antibody titer z‐scores for each of the four groups. Physical activity was evaluated based on reported frequency and intensity of physical activity conducted in the last month. Participants were grouped into three categories: adequately physically active, inadequately physically active, and inactive. The outcomes were IgG cluster scores with physical activity as the predictor. Multivariable models adjusted for age, sex, race, smoking status, waist circumference, education, poverty‐income‐ratio, alcohol, and diabetes. Results: In adjusted models, physical activity was positively associated with the antibodies in the Orange‐Blue cluster ( E. nodatum, A. naeslundii ), a cluster that is associated with healthy periodontal states. The mean differences in cluster scores were 15.2 (95% CI −1.0, 31.4) for Model 3, and 7.0 (95% CI −8.3, 22.3) for Model 4 comparing the sufficiently active group to the inactive group. Conclusions: Antibody titers against periodontal microorganisms reflecting good oral health trended higher among physically active individuals, but the results were not statistically significant at the 0.05 level.